(untitled) (Research, Society and Development, 2024)
Introduction: Covid-19 is a disease caused by the new coronavirus, called SARS-CoV-2, an RNA virus, which presents a clinical spectrum ranging from asymptomatic infections to severe acute respiratory failure. Responsible for more than 421,316 deaths in Brazil since its discovery. Studies show significant differences between surviving and non-surviving patients related to total lymphocyte count, urea, CRP levels and D-dimer at admission, and non-surviving patients presented numerous alterations, including hypernatremia. The objective of the study is to review the bibliographical analysis of hypernatremia in patients with a confirmed diagnosis of Covid-19. Method: This is a literature review with searches in the Scielo and Pubmed databases for articles from the last 5 years that met the established inclusion criteria. Results and Discussion: Hospital studies report increased mortality in intensive care units associated with hypernatremia. Evidencing an association between hypernatremia and a higher mortality rate for patients with pneumonia in general. Hypernatremia is often a reflection of water loss rather than sodium gain, mainly due to dehydration due to increased body temperature. Conclusion: Hypernatremic patients have a higher rate of adverse effects such as thrombotic events and an increased mortality rate. Hypernatremia control protocols are encouraged.